2014
DOI: 10.1177/0310057x1404200504
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Consequences: A Review of Discharge Opioid Prescribing for ongoing Management of Acute Pain

Abstract: Over recent years there has been a growing need for patients to be sent home from hospital with prescribed opioids for ongoing management of their acute pain. Increasingly complex surgery is being performed on a day-stay or 23-hour-stay basis and inpatients after major surgery and trauma are now discharged at a much earlier stage than in the past. However, prescription of opioids to be self-administered at home is not without risk. In addition to the potential for acute adverse effects, including opioid-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 120 publications
2
91
1
Order By: Relevance
“…When patients are discharged from hospital with opioids, it is important that they understand the risk that use of these medications brings. It is vital that patients receive information and advice to ensure they take their opioid medication safely after leaving hospital and that expectations around the duration of use and ongoing treatment are managed appropriately . This information should be supplied in both verbal and written form.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When patients are discharged from hospital with opioids, it is important that they understand the risk that use of these medications brings. It is vital that patients receive information and advice to ensure they take their opioid medication safely after leaving hospital and that expectations around the duration of use and ongoing treatment are managed appropriately . This information should be supplied in both verbal and written form.…”
Section: Discussionsupporting
confidence: 89%
“…The online survey was developed using Qualtrics survey software (Qualtrics, LLC, Provo, UT, USA). Questions were formulated based on work done by the Victorian Department of Health and Human Services and the current literature . The survey (Appendix ) collected descriptive hospital information, including hospital size, location (rural/regional or metropolitan), whether privately or publicly funded and whether the service had a pharmacy department, as well as the respondent's role at the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Macintyre et al have recently reported that large quantities of opioids are being prescribed upon hospital discharge, yet a significant amount remains unconsumed, resulting in a potentially large pool of unused opioids available for later use by either the patient or others in the community. 25 With the large amounts of morphine prescribed and hence dispensed into homes comes an increasing potential for medication errors, abuse, and intoxications. 15,26,27 Lovegrove et al 26 estimated that between 2007 and 2011, there were 9490 hospitalizations annually in the US due to unsupervised ingestion of oral medications among children under age 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate risks of opioid abuse and dependency, assessing patients for risk of opioid abuse with a screening tool, reducing the dose as the pain abates, and educating patients that opioids will be administered for a limited period are suggested (Macintyre, Huxtable, Flint, & Dobbin, 2014). Appropriate weaning from opioids (Chou et al, 2016; Washington State Agency Medical Directors' Group, 2015) could prevent withdrawal symptoms and therefore misuse, because patients may administer opioids to prevent the experience of withdrawal when pain is no longer present.…”
Section: Patient Assessment and Communicationmentioning
confidence: 99%
“…Appropriate weaning from opioids (Chou et al, 2016; Washington State Agency Medical Directors' Group, 2015) could prevent withdrawal symptoms and therefore misuse, because patients may administer opioids to prevent the experience of withdrawal when pain is no longer present. Discussions of patient expectations and assessing the risk of opioid abuse have the potential to improve patient satisfaction and safe care (Browne, Andrews, Schug, & Wood, 2011; Georgy et al, 2011; Macintyre et al, 2014). …”
Section: Patient Assessment and Communicationmentioning
confidence: 99%